Prenatal alcohol exposure among Alaska Native/American Indian infants - Khan, Burhan A. (Co-Action Publishing, 2013)
BACKGROUND: Recent reports indicate a decline in rates of Fetal Alcohol Syndrome (FAS) among Alaska Native and American Indian (AN/AI) infants. Nevertheless, AN/AI infants remain disproportionately impacted by the effects of prenatal alcohol exposure. METHODS: AN/AI pregnant women in their 3rd trimester completed a questionnaire on demographic data and the amount and frequency of their alcohol consumption in the month prior to conception and during pregnancy. Differences across demographics and trimesters were tested with the Chi-square, Fisher's exact or McNemar's test as appropriate. RESULTS: Of the 125 participants, 56% (n=71) reported no alcohol consumption in the 1st through 3rd trimesters of pregnancy; 30% (n=38) of the 125 participants also reported no alcohol consumption in the month before pregnancy. Of the 43% (n=54) who reported consuming alcohol during pregnancy (1st, 2nd and/or 3rd trimester), most (35%) reported alcohol use only in the 1st trimester. Binge drinking in the 1st or 2nd trimester was reported amongst 20% (n=25) of participants with an additional 18% (n=29) reporting binge drinking in the month prior to pregnancy. Women who reported pre-conception binge drinking were significantly more likely to report binge drinking during their 1st trimester (p<0.0001) and 2nd trimester (p<0.0001). A history of tobacco use (p=0.0403) and cigarette smoking during pregnancy (p<0.0001) were also associated with binge drinking during pregnancy. CONCLUSION: Among study participants, reported use of alcohol was primarily limited to pre-conception and the 1st trimester, with a dramatic decrease in the 2nd and 3rd trimesters. Prevention programmes, such as the Alaska FAS Prevention Project, may have contributed to observed decreases in the 2nd and 3rd trimesters. Additional study and focus on pre-conception, the 1st trimester and binge drinking, as well as tobacco use might augment Fetal Alcohol Spectrum Disorder prevention efforts.